(untitled) (De Musica, 2021)
Mobile phones and the Internet combined have led to the creation of applications that allow their users to perform music using only their Smartphones. With the Smule applications that we analyze in this paper, people can sing karaoke together with other singers from all over the world, or play a tune with their fingertips tapping on a phone’s screen. Besides providing new entertainment activities, the Smule applications and their multiple options regarding audio and video editing can bring about new musical practices and musical artifacts. Smule users can sing duets remotely, without actually singing on the same time – a virtual collective performance. Singing karaoke becomes a solitary practice where togetherness is contrived but not achieved. Video recordings can be edited and shared on a built-in social network, thus being endorsed with a new function: to create bonds within a social network. Analyzing the discourses of Smule creators and developers, we also show that the applications do not achieve what they are promised to do, namely providing social and authentic practices.